2002
DOI: 10.1002/1521-3994(200210)323:5<462::aid-asna462>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The V light curve of eclipsing binary LD355 was analyzed by using the latest version of Wilson Program in order to derive photometric elements of this system. Since no spectroscopic mass ratio is available, the q‐search method was applied to yield the preliminary range of mass ratio in order to search for the final solution. The solution was performed by assuming detached (mode 2) and semi‐detached (mode 5) configurations, since no classification of the system based on the shape of light curve is possible. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Taking the total mass (M 1 + M 2 ) of the eclipsing pair to be 1.64 + 0.5 = 2.14 M (Pazhouhesh and Edalati (2002)) and assuming that the orbit of third body is co-planar with the orbit of eclipsing pair we obtained the mass of the hypothetical third body as 0.378 ± 0.022 M . With the Hipparcos distance of V839 Oph d = 123.61 pc, we may easily calculate the maximum angular separation between the third body and eclipsing pair as 0 .073 ± 0 .014.…”
Section: Observations and O-c Diagramsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking the total mass (M 1 + M 2 ) of the eclipsing pair to be 1.64 + 0.5 = 2.14 M (Pazhouhesh and Edalati (2002)) and assuming that the orbit of third body is co-planar with the orbit of eclipsing pair we obtained the mass of the hypothetical third body as 0.378 ± 0.022 M . With the Hipparcos distance of V839 Oph d = 123.61 pc, we may easily calculate the maximum angular separation between the third body and eclipsing pair as 0 .073 ± 0 .014.…”
Section: Observations and O-c Diagramsmentioning
confidence: 99%
“…The variability and the light curve variation of V839 Oph (BD +9 • 3584, HD166231, V min = 8 m .8, V max = 9 m .39) as W UMa type system were determined by Rigollet (1947). The first photoelectric light curves of this system were obtained by Binnendijk (1960).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations were made in the past years, giving times of minima and the ephemeris of the system (Binnendijk, 1960;Hilditch and Hill, 1975;Lafta and Grainger, 1985;Agerer and Huebsher, 1997). Niarchos (1989), Akalin and Derman (1997), Pazhouhesh et al (2001) and Pazhouhesh and Edalati (2003) presented a model of the system, based on their observations. Wolf (1996) analyzed in detail the O-C values and concluded that the system undergoes changes of its orbital period, a result also found by Akalin and Derman (1997).…”
Section: Introductionmentioning
confidence: 99%